Study the Effect of the Laser on the Structural and Electrical Properties of the Compound Tl2-xHgxBa2-ySryCa2Cu3O10 + δ Superior Electrical Conductivity at High Temperatures - Abdul Kareem Dahas Ali; Sabah Jalal Fathi; Noor Abdul Wahed Ahmed (Tikrit Journal of Pure Science)
This study included the preparation of composite samples (Tl2-xHgxBa2-ySryCa2Cu3O10+δ) in various concentrations of x where (x=0,0.1,0.2,0.3,0.4,0.5). by solid state reaction method and under hydrostatic pressure (ton /cm2 8 interaction) and temperature annealing (850°C), and determine the effect of the laser on the structural and electrical properties elements in the compound, Observed by examining the XRD The best ratio of compensation for x is 0.2 as the value of a= b = 5.3899 (Å), c = 36.21 (Å) show that the installation of Teragonal structure, the study found that oxygen played an important role in increasing the critical temperature. When you shine a CO2 laser on the samples in order to recognize the effect of the laser on these samples  showed the study of X-ray diffraction of these samples when preparing samples with different concentrations of the values ​​of x, the best value of compensation is 0.2 which showed an increase in the values ​​of the dimensions of the unit cell a = b = 5.3929 (Å), c = 36.238 (Å) as well as we have noticed in the Teragonal structure of the compound and took the boat the best role in the crystal structure. When examining the electrical characteristics for different values of the values of (x) found that the best degree of critical temperature at x = 0.2 is TC = 142 K and after shedding CO2 laser on the prepared forms note the increase in the critical temperature at x= 0.2 is TC = 144 K. The screening samples by atomic force microscopy three-dimensional (AFM), and also has a study and examination of the crystal structure of the samples by scanning electron microscope (SEM) and know the percentages elements in the compound and, the effect of annealing temperature .the pressure applied, and to quantify the concentration of elements in the composite.